KEBIJAKAN PEMEKARAN DAERAH DALAM BINGKAI OTONOMI KHUSUS: STUDI KASUS PROVINSI PAPUA SELATAN - Novia Eka Ardani; Muhammad Adri Ramadhan; Yakoba Faleria Ome Yanengga; Umiyati Haris (Papsel Journal of Humanities and Policy, 2025)
The establishment of the South Papua Province is a strategic step to address the development inequality that exists in Papua. This study examines the role of various stakeholders in the process of regional expansion using a qualitative literature review. The results of the study highlight the importance of an approach that involves participation, protection of indigenous peoples rights, and transparent budget management. The suggestions provided include gradual expansion and the establishment of an independent supervisory board. This study contributes to the literature on regional autonomy by combining the perspectives of various actors involved. Keywords: Regional Autonomy, Development Inequality, Role of Stakeholders, Rights of Indigenous Peoples, Budget Transparency